2018
DOI: 10.7326/m17-2073
|View full text |Cite
|
Sign up to set email alerts
|

Use of Immune Checkpoint Inhibitors in the Treatment of Patients With Cancer and Preexisting Autoimmune Disease

Abstract: National Institute of Arthritis and Musculoskeletal and Skin Diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
245
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 386 publications
(254 citation statements)
references
References 68 publications
6
245
2
1
Order By: Relevance
“…A few other smaller case series have also reported on the frequency of disease flares and de novo IRAEs in patients with prior autoimmune disease receiving ICIs as treatment for concomitant cancer . Results have generally been similar to those reported by Tison et al, with approximately half of the patients developing a flare.…”
supporting
confidence: 75%
“…A few other smaller case series have also reported on the frequency of disease flares and de novo IRAEs in patients with prior autoimmune disease receiving ICIs as treatment for concomitant cancer . Results have generally been similar to those reported by Tison et al, with approximately half of the patients developing a flare.…”
supporting
confidence: 75%
“…The authors concluded that clinicians should take the severity of a patient's underlying AD into account before they administer ICI therapy, and they should also monitor these patients very closely during treatment and after treatment discontinuation. 3 Moreover, the authors suggested that patients should be duly informed with respect to both the risks and benefits of ICI treatment.…”
Section: Icis and Patients With Ad (General)mentioning
confidence: 99%
“…1 Monoclonal antibodies that block these pathways allow the body to target cancer cells with fewer restraints. 3 Since 2011, the Food and Drug Administration has approved 6 checkpoint inhibitors for use in many different types of cancer (see Table 1). Anti-CTLA-4 antibodies block receptor activation and thereby allow resident T-cells to mount a more effective antitumor response.…”
Section: Introduction: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most patients with preexisting inflammatory or autoimmune disease have been excluded from clinical trials of ICIs. Some case reports and small series, as well as a meta‐analysis assessing the use of ICIs in such populations, have been published recently, but more robust data on the safety of ICI therapy in larger cohorts of patients with preexisting autoimmune disease are needed . Whether the occurrence of IRAEs is associated with better antitumor response is a matter of debate .…”
Section: Introductionmentioning
confidence: 99%